Prediction of Displacement and Stress Values of Composite Materials Under Load with Machine Learning Models - Ferati, Kajs; Adar, Nurettin Gökhan (Osman SAĞDIÇ, 2022)
In this study, the determination of displacement and stress values under certain load of glass fiber and epoxy resin laminated reinforced composite materials by using machine learning models is targeted. In the scope of study, the modelling is done by changing the material properties of varied laminations of composite samples via Ansys software and a tensile force is implemented in order to receive the total deformation and Von Misses stresses under the implemented tensile force and creation of the dataset is completed. The robust linear regression and Gaussian process regression models from machine learning algorithms are used to predict and determine the total deformation and Von Misses stresses by training and testing the models with the dataset created. As result, the predicted values obtained from trained and tested regression models and the real values obtained by modelling in Ansys are compared. Additionally, in consideration of model parameters for both regression models, the evaluation of true responses and correct prediction/determination is done. According to the results, Gaussian process regression model is determined as a better model for related study.

Bu çalışmada, makine öğrenmesi modelleri kullanılarak cam elyaf ve epoksi reçine takviyeli lamine kompozit malzemelerin yer değiştirme ve gerilme değerlerinin tahmin edilebilmesi hedeflenmiştir. Çalışma kapsamında, kesiti belirlenen numune farklı laminasyonlar için malzeme özellikleri değiştirilerek modellenmiş ve Ansys yazılımı ile uygulanan çekme kuvveti altında toplam yer değiştirme ve Von Misses gerilmeleri ile veri seti oluşturulmuştur. Oluşturulan veri seti ile makine öğrenmesi modelleri olan Sağlam regresyon ve Gauss işlemci regresyonu modelleri kullanılarak toplam yer değiştirme ve Von Misses gerilmelerinin tahmin edilmesi sağlanmıştır. Sonuç olarak, Ansys yazılımı ile elde edilen ve eğitim ve test amacıyla kullanılan veri seti değerleri ile her iki modelden elde edilen aynı değerlerin kıyaslaması yapılmıştır. Ayrıca, iki modele ait modellerin çalışma parametreleri göz önünde bulundurularak doğruluk oranı açısında değerlendirmesi gerçekleştirilmiştir. Sonuçlara göre, Gauss işlemci regresyon modelinin ilgili çalışma açısında daha uygun olduğu belirlenmiştir.
Makine Öğrenmesi ile Kompozit Malzemelerin Yük Altındaki Yer Değiştirme ve Gerilme Değerlerinin Tahmini
Keywords: Engineering; Mühendislik